EFFECT OF PROGESTERONE IN LOWERING MATERNAL PLASMA CORTICOTROPIN-RELEASING HORMONE IN PATIENTS WITH PRETERM LABOR (Iraqi Journal of Medical Sciences, 2019)
Background: Preterm labor is a major obstetrics problem because it associated with high morbidity and mortality to the born baby. Many studies were done to study different aspects of its risk factors, diagnosis and treatment to decrease its incidence, bad sequel to the fetus and recurrence.Objective: To evaluate the role of progesterone in lowering CRH level in plasma of patient with preterm labor.Methods: This study is a case control study. Forty-five pregnant women with preterm labor were included in the study and basal plasma Corticotropin releasing hormone (CRH) level was done for each patient. All patients were given oral tocolytic drug, with an initial bolus of 20 mg Nifedipine followed by 10 mg three times daily. They received betamethasone injection (12 mg) 24 hours after hospitalization. Then after stabilization of each patient with random selection, 25 patients were included in group (1) and were given progesterone injection. Twenty patients were included in group (2) or control group because no progesterone injection was given to them. After 24 hours of admission to the hospital, plasma CRH level was measured for both groups with evaluation of the outcome of each patient with preterm labor.Results: Progesterone is more effective in lowering CRH level in patients with preterm labor. In study of 45 cases of preterm labor, the mean CRH level of group (1) decreased from 33.41 ng/ml to 22.12 ng/ml, while the mean level of it in group (2) increased from 27.44 ng/ml to 28.54 ng/ml. Conclusion:Progesterone treatment is effective in lowering CRH level in patients with preterm labor. This would have a positive effect in prolonging the pregnancy period in these patients.Keywords: Preterm labor, progesterone, CRHCitation: Yaseen EM, Abd AF. Effect of progesterone in lowering maternal plasma corticotropin-releasing hormone in patients with preterm labor. Iraqi JMS. 2019; 17(1): 32-42. doi: 10.22578/IJMS.17.1.6
Keywords: Preterm labor; progesterone; CRH